Hidden species diversity in Marcusenius moorii (Teleostei: Mormyridae) from the Congo Basin. Issue 5 (13th February 2020) - Mambo Baba, Taylor; Kisekelwa, Tchalondawa; Danadu Mizani, Célestin; Decru, Eva; Vreven, Emmanuel
Abstract: New collections from the Yangambi Biosphere Reserve (YBR) and Okapi Wildlife Reserve (OWR) revealed the presence of two groups of specimens similar to, but different from Marcusenius moorii . To study both these groups, an integrated morphological and genetic (mtDNA, cytb ) approach was used. This study revealed that one of the two groups is conspecific with Marcusenius lambouri, a junior synonym of M. moorii, which is herein revalidated, with M. moorii longulus as its junior synonym. Marcusenius lambouri differs from M. moorii by a higher number of lateral line scales (44–46 vs . 40–43), a shorter pectoral‐fin length (14.6–19.9 vs . 20.3–25.2% standard length; L S ) and a more elongated body due to a usually shallower middle body depth (19.8–26.5 vs . 26.3–35.9% L S ). The other group revealed to be a new species for science, Marcusenius verheyenorum, which can be distinguished from its congeners with eight circumpeduncular scales by the following unique combination of characters: a rounded head with a terminal mouth; a short and deep caudal peduncle (middle caudal‐peduncle depth, 44.9–54.6% caudal‐peduncle length; L CP ), a deep body (middle body depth, 27.7–34.2% L S ), 38–43 scales on the lateral line, 40–41 vertebrae, 20–21 dorsal‐fin rays and 26 anal‐fin rays. Some specimens previously attributed to M. moorii were examined and reassigned to M. lambouri or M. verheyenorum . As a result, M. moorii and M. lambouri occur in sympatry in the middle Congo Basin, with the distribution area of M. moorii still further extending into the lower Congo Basin. Instead, the distribution of M. verheyenorum is limited to some right bank tributaries of the upstream part of the middle Congo Basin. Two museum records from the Lilanda River (YBR), collected in the 1950s and previously identified as M. moorii, were re‐identified as belonging to the new species, M. verheyenorum . However, the species now seems locally extinct in that region, which reflects the significant anthropogenic effects even within this reserve.